2022
DOI: 10.3390/jpm12030498
|View full text |Cite
|
Sign up to set email alerts
|

Women’s Experiences with Compliance with Pelvic Floor Home Exercise Therapy and Lifestyle Changes for Pelvic Organ Prolapse Symptoms: A Qualitative Study

Abstract: In this study, we aimed to investigate women’s experiences with compliance with prescribed pelvic floor muscle exercises (PFMEs) and lifestyle changes 6–12 months after completing an individual pelvic floor physiotherapy program. This study was targeted to understanding factors affecting adherence to PFMEs and lifestyle changes to deal with pelvic organ prolapse (POP) symptoms. We designed this research as a descriptive qualitative study. We conducted this study from December 2016 to September 2017 in Madrid, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…Similar results were found in the postpartum population [ 55 ]. Previous studies have also shown that a sense of responsibility and the need to take care of others are the biggest barriers for women to adhere to pelvic floor muscle exercises [ 56 ]. This is due to the fact that in Eastern countries, married women are expected to take on not only more housework while working long hours, but are also expected to play the roles of raising children and taking care of the elderly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were found in the postpartum population [ 55 ]. Previous studies have also shown that a sense of responsibility and the need to take care of others are the biggest barriers for women to adhere to pelvic floor muscle exercises [ 56 ]. This is due to the fact that in Eastern countries, married women are expected to take on not only more housework while working long hours, but are also expected to play the roles of raising children and taking care of the elderly [ 57 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies that conducted a follow-up after the intervention reported women’s perseverance in terms of the newly-acquired voiding habits [ 16 ] and PFM exercises [ 15 , 16 ], even though the follow-up was not supervised by professionals. Periodic face-to-face follow-up meetings may contribute to promoting adherence to the exercise programme or healthy behaviours, correcting misconceptions, answering questions, or modifying exercises based on individual progression [ 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…If a woman is not motivated to adhere, the effectiveness of the PFMT and the subjective improvement will be limited. One study in Spain showed that most women, over time, do not perform regular pelvic floor muscle exercises [21].…”
Section: Primary Outcomesmentioning
confidence: 99%